The Platform trial In COVID-19 vaccine priming and BOOsting (PICOBOO) booster vaccination substudy protocol - McLeod C; Dymock M; Flanagan KL; Plebanski M; Marshall H; Marsh J; Estcourt MJ; Ramsay J; Wadia U; Williams PCM; Tjiam MC; Blyth C; et al. (Trials)
Abstract Background Coronavirus-2019 (COVID-19) vaccination in Australia commenced in February 2021. The first vaccines recommended for use were AZD1222 and BNT162b2, both delivered as a two-dose primary schedule. In the absence of sustained immunity following immunisation, recommendations for booster vaccination have followed. It is likely that periodic boosting will be necessary for at least some Australians, but it is unknown what the optimal booster vaccines and schedules are or for whom vaccination should be recommended. Methods The Platform Trial In COVID-19 priming and BOOsting (PICOBOO) is a multi-site, multi-arm, randomised, Bayesian adaptive platform trial evaluating different booster vaccine interventions in immunocompetent children and adults, stratified by their primary vaccination schedule and age. Participants are randomised to receive one of three licensed COVID-19 booster vaccines available for use in Australia. PICOBOO aims to generate evidence about the immunogenicity, reactogenicity, and cross-protection of different booster vaccine strategies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants/subvariants. The protocol structure specifying PICOBOO is modular and hierarchical. We have previously published the PICOBOO core (master) protocol. Here, we detail the substudy protocol which outlines the study processes which are specific to PICOBOO participants enrolled in the booster vaccination substudy. Discussion PICOBOO is an adaptive platform trial evaluating different COVID-19 booster vaccination strategies to generate evidence to inform immunisation practice and policy. The modular and flexible protocol structure is intended to enable investigators to respond with agility to new research questions as they arise, such as immunogenicity targeting emergent virus variants, and the immunogenicity and reactogenicity of new vaccines as they become available for use. Trial registration Australian and New Zealand Clinical Trials Register ACTRN12622000238774; registered on 10/02/2022. Protocol V8.0_23112023.